Advances in manufacturing spinal cord implant using 3D selective laser induced etching of fused silica (Transactions on Additive Manufacturing Meets Medicine, 2021)
Spinal cord injury (SCI) results in its dysfunction and can lead to permanent paralysis. We developed a mechanical microconnector system (mMS) to support regeneration after the SCI. This paper describes a new fabrication process of the mMS using selective laser induced etching (SLE). This technique enables the 3D microstructuring of fused silica and promises rapid and highly individualizable mMS. We show that the SLE process enhances the fabrication with regard to complexity, speed and quality. An individual mMS is produced in less than 48h hours with structures from 4µm to 1mm.
Keywords: Spinal Cord Injury; Implant; Selective Laser Induced Etching; 3D Microstructuring; Fused Silica